Fluids or vasopressors for the initial resuscitation of septic shock - Macdonald, Stephen; Peake, Sandra L.; Corfield, Alasdair R.; Delaney, Anthony (Frontiers in Medicine, 2022)
Intravenous fluid resuscitation is recommended first-line treatment for sepsis-associated hypotension and/or hypoperfusion. The rationale is to restore circulating volume and optimise cardiac output in the setting of shock. Nonetheless, there is limited high-level evidence to support this practice. Over the past decade emerging evidence of harm associated with large volume fluid resuscitation among patients with septic shock has led to calls for a more conservative approach. Specifically, clinical trials undertaken in Africa have found harm associated with initial fluid resuscitation in the setting of infection and hypoperfusion. While translating these findings to practice in other settings is problematic, there has been a re-appraisal of current practice with some recommending earlier use of vasopressors rather than repeated fluid boluses as an alternative to restore perfusion in septic shock. There is consequently uncertainty and variation in practice. The question of fluids or vasopressors for initial resuscitation in septic shock is the subject of international multicentre clinical trials.